If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -1(12 + -3x) = -6x + -12 + 3x -6 + (12 * -1 + -3x * -1) = -6x + -12 + 3x -6 + (-12 + 3x) = -6x + -12 + 3x Combine like terms: -6 + -12 = -18 -18 + 3x = -6x + -12 + 3x Reorder the terms: -18 + 3x = -12 + -6x + 3x Combine like terms: -6x + 3x = -3x -18 + 3x = -12 + -3x Solving -18 + 3x = -12 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -18 + 3x + 3x = -12 + -3x + 3x Combine like terms: 3x + 3x = 6x -18 + 6x = -12 + -3x + 3x Combine like terms: -3x + 3x = 0 -18 + 6x = -12 + 0 -18 + 6x = -12 Add '18' to each side of the equation. -18 + 18 + 6x = -12 + 18 Combine like terms: -18 + 18 = 0 0 + 6x = -12 + 18 6x = -12 + 18 Combine like terms: -12 + 18 = 6 6x = 6 Divide each side by '6'. x = 1 Simplifying x = 1
| (12t-6y)0=0 | | x*4x=8*x+12 | | (x-2)(y-4)=18 | | Y-(2y+3)=8y | | -3(2u-3x-4)= | | 16s=-48 | | 15=3+7 | | x*12=x-1*14 | | -45=6(-3f-4) | | Y-10=-19 | | w^2+99=0 | | 4*9=x*(9+x) | | 2x-6=7-2x | | 13(z+2)-4(z-4)=4(z-1)+4(z-4) | | -t+63=21 | | x*4x=8*8+x+4 | | 4bsquared=7b | | 3+5(4z+6)=2z-3 | | 38=-2(21-z)+4(z-4) | | x*4x=8*12+x | | kx^2-2kx+4=x^2 | | 8.25m-m=1.45 | | 12y^2+7y=-10 | | 2(x+1)=8(x-2)-18 | | 520=x^2+27x | | 5x-(-3)=3 | | w^3+5w^2+3w-113=0 | | 520=x^2*27x | | (3y^4z^3-5y^6)(-4yz^5)= | | 3w^2-12w+98=0 | | 4x^2=64x*256 | | 684=4(x+16) |